2007
DOI: 10.1002/bem.20386
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in rats after long‐term exposure to GSM‐900 mobile phone radiation

Abstract: Considering the frequent use of mobile phones, we have directed attention to possible implications on cognitive functions. In this study we investigated in a rat model the long-term effects of protracted exposure to Global System for Mobile Communication-900 MHz (GSM-900) radiation. Out of a total of 56 rats, 32 were exposed for 2 h each week for 55 weeks to radio-frequency electromagnetic radiation at different SAR levels (0.6 and 60 mW/kg at the initiation of the experimental period) emitted by a (GSM-900) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 36 publications
4
54
1
6
Order By: Relevance
“…We have previously seen in the same animals that the performance in the test trial of the episodic-like memory test (as seen by the standardised difference between old familiar object exploration time and recent familiar object exploration time) is significantly impaired in the GSM exposed animals as compared to the sham exposed animals [17]. There was no statistically significant difference in the exploration time between the higher and lower GSM exposed animals.…”
Section: Individual Correlation Between Memory and Behavioural Functimentioning
confidence: 77%
See 4 more Smart Citations
“…We have previously seen in the same animals that the performance in the test trial of the episodic-like memory test (as seen by the standardised difference between old familiar object exploration time and recent familiar object exploration time) is significantly impaired in the GSM exposed animals as compared to the sham exposed animals [17]. There was no statistically significant difference in the exploration time between the higher and lower GSM exposed animals.…”
Section: Individual Correlation Between Memory and Behavioural Functimentioning
confidence: 77%
“…These TEM-cells have been designed by dimensional scaling from previously constructed cells at the National Bureau of Standards [6], which are known to generate uniform TEM-fields for standard measurements. The experimental setup has been described in detail in the first part of the present long term study that reported on cognitive effect after repeated exposure [17]. In short, a GSM mobile test phone with a programmable power output, at the frequency of 900 MHz, was connected to a power splitter, which divides the power into equal parts fed into the four TEM-cells used.…”
Section: Gsm Exposurementioning
confidence: 99%
See 3 more Smart Citations